1,3,4-Thiadiazole and 1,2,4-triazole-3(4 H )-thione bearing salicylate moiety: synthesis and evaluation as anti- Candida albicans - Awwad Abdoh Radwan; Fares Kaed Alanazi; Mohammed Hamed Al-Agamy (Universidade de São Paulo, 2017)
Abstract Dramatically increased occurrence of both superficial and invasive fungal infections has been observed. Candida albicans appear to be the main etiological agent of invasive fungal infections. The anti-C. albicans activity of thiosemicarbazide, 1,3,4-Thiadiazole, and 1,2,4-triazole-3(4H)-thione compounds (compounds 3-23) were investigated. The MIC values of thiadiazole and triazole derivatives 10-23 were in the range of 0.08-0.17 µmol mL-1, while that of fluconazole was 0.052 µmol mL-1. Compound 11 (5-(2-(4-chlorobenzyloxy)phenyl)-N-allyl-1,3,4-thiadiazol-2-amine) and compound 18 (5-(2-(4-chlorobenzyloxy)phenyl)-4-allyl-2H-1,2,4-triazole-3(4H)-thione) were found to be the most active compounds, with MIC values of 0.08 µmol mL-1. The newly synthesized thiadiazole and triazole compounds (compounds 10-23) showed promising anti-Candida activity. The allyl substituent-bearing compounds 11 and 18 exhibited significant anti-Candida albicans activity and showed a binding mode as well as the fluconazole x-ray structure.